Factors associated with beliefs about adherence to non-pharmacological treatment of patients with heart failure - Izabel Cristina Ribeiro da Silva Saccomann; Fernanda Aparecida Cintra; Maria Cecília Bueno Jayme Gallani (Revista da Escola de Enfermagem da USP, 2014)
This study aimed at assessing beliefs about the benefits and barriers to adherence to daily self-monitoring of weight/edema in patients with heart failure, and the influence of demographic and clinical variables on those beliefs. 105 patients were interviewed. The mean of the subscales Benefits and Barriers were 20.2 (± 5.7) and 30.1 (±7.1), respectively. Patients perceived that adherence to daily self-monitoring of weight/edema could keep them healthy, improve their quality of life and decrease the chances of readmission. Approximately half of patients (46.7%) reported forgetting this measure. Those who controlled weight once a month were more likely to have barriers to adherence (OR= 6.6; IC 95% 1.9-13.8; p=0.01), showing this measure to be the main factor related to perceived barriers. Education in health can contribute with the development of strategies aimed at lowering barriers and increasing benefits of this control.